A new species of "Lithasia"(Mollusca: Caenogastropoda: Pleuroceridae) from the Harpeth River, Tennessee, U.S.A. - Minton, Russell L.; Savarese, Steven P.; Campbell, David C. (Zootaxa, 2005)
A species of pleurocerid snail, Lithasia spicula sp. nov., is described from two groups of specimens taken from the Harpeth River, Tennessee near Bellevue. The species resembles Li. armigera (Say, 1821) conchologically, but molecular analyses group it either with the polyphyletic assemblage currently considered Leptoxis or as a separate lineage in Pleuroceridae. The species also possesses a unique radula, and is the first known pleurocerid endemic to the Harpeth River.